The Analysis of Total Phenolic Content of Siam Weed Leaf Extract (Chromolaena Odorata L.) and Antibacterial Activity Test Against Escherichia coli and Staphylococcus aureus - yusriadi tamuddin; Mega Fia Lestari; Hasri Hasri; Maryono Maryono; Netti Herawati (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2022)
This study aims to determine the total phenolic content of extracts of water, methanol, and ethyl acetate of Siamese weed leaves and to test their bioactivity against Escherichia coli and Staphylococcus aureus. This research includes testing of active compound groups and determination of total phenolic and bioactivity tests. The total phenolic content was determined by the Folin-Ciocalteu method using a UV-Vis spectrophotometer. The results of the analysis showed that the extracts of water, methanol, and ethyl acetate were 54.0647; 44.9289; and 9.2005 mg GAE/g extract. The results of the bioactivity test of aqueous extracts were greater than that of methanol and ethyl acetate extracts where the minimum inhibitory concentration (MIC) of aqueous extracts against E. coli bacteria was at a concentration of 0.1%, while against S. aureus bacteria the bioactivity of methanol extracts was greater than that of aqueous extracts and ethyl acetate concentrations. minimum inhibitory (MIC) 0.5%. Keywords: Antibacterial, Siamese weed leaves, total phenolic.